Nossiter, T.J., Communism in Kerala. A Study in Political Adaptation, Berkeley y Los Angeles, University of California Press, para el Royal Institute of International Affairs, Londres, 1928, pp. XIII-356. - Annand P. Ghildyal (El Colegio de México, A.C., 1984)
-